Rentabilidad, inflación y devaluación : aplicación a los fondos mutuos bbva cash soles y dólares Perú (2016-2019) - Pando, Enrique (2020)
In the last 3 years, mutual funds for securities investment represented an alternative for more than 400 thousand participants, whose preferences were mainly concentrated in BBVA Cash Soles and Dollars funds. The main cause of this concentration is in the conservative profile of the Peruvian investor, which requires evaluating the profitability of the funds mentioned in comparison with that offered by bank term deposits. For this, the present note takes into account periodic inflation and exchange devaluation for the determination of real profitability and equivalent profitability in soles respectively. Subsequently, the returns obtained are compared and finally, the conclusions are presented.